A Case Of Panic Disorder With Agoraphobia Effectively Treated Via Cognitive Behavior Hypnotherapy - Rohayah, Husain; Khairi, Che Mat (2015)
This is a case of 36-year old, account officer, presented with multiple panic attacks associated with excessive fear of being in public places for three months. Consequently she was unable to drive to work and limited her outside activities. Further history revealed that she had involved in a minor car accident a year ago. At baseline, she had high level of anxiety with subjective unit of distress (SUD) score of 9 out of 10 and Beck Anxiety Inventory (BAI) of 40. The goals of therapy were to stabilize her panic attacks, anxiety and fears via cognitive behavioural hypnotherapy, modifying and reframing her negative thinking and improving her function especially the ability to drive on her own. The therapy started with training her to achieve relaxed state via imagery and self-hypnosis; then gradually exposed her to the feared situation via systematic hypno-desensitization. She was trained on effective breathing technique to control the panic attacks with ego strengthening. She gradually improved after 6 therapy sessions and came for another 3 booster sessions with SUDs of 2